Pengaruh Alelopati Jarak Pagar (Jatropha curcas L.) terhadap Perkecambahan Benih Jagung, Tomat dan Padi Gogo - Ince Raden; Bambang S. Purwoko; Edi Santosa; , Hariyadi; Munif Ghulamahdi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The objective of this research was to evaluate the effect of extract of leaves, seed and root of physic nut on the germination of corn, tomato, and upland rice. Research was conducted by using Complete Randomized Block Design with two factors, i.e., plant organ (leaves, seed and root) and species (corn, tomato and upland rice). The results showed that extract of 36 g dried organ/200 ml water (0.18 g/ml water) affected seed germination of corn, tomato, and upland rice. Extract of leaves tended to reduce percentage of corn seed germination (55.30% vs 70.68%), and extract of root to reduce germination of tomato and upland rice, 52.70% and 68.67%, compared to control 76% and 84%, respectively.   Key words:  Plant organ extract, physic nut, germination